Translating knowledge from Pakistan's second generation surveillance system to other global contexts. (20th December 2012) - Adrien, Alix; Thompson, Laura H; Archibald, Chris P; Sandstrom, Paul A; Munro, Michelle; Emmanuel, Faran; Blanchard, James F
Abstract : Background: From 2004 to 2011, a collaborative project was undertaken to enhance the capacity of the Government of Pakistan to implement an effective second-generation surveillance system for HIV/AIDS, known as the HIV/AIDS Surveillance Project (HASP). In four separate rounds, behavioural questionnaires were administered among injection drug users, and female, male and hijra (transgender) sex workers. Dried blood spots were collected for HIV testing. Methods: Through interviews with project staff in Pakistan and Canada, we have undertaken a critical review of the role of HASP in generating, using and translating knowledge, with an emphasis on capacity building within both the donor and recipient countries. We also documented ongoing and future opportunities for the translation of knowledge produced through HASP. Results: Knowledge translation activities have included educational workshops and consultations held in places as diverse as Colombia and Cairo, and the implementation of HASP methodologies in Asia, the Middle East and sub-Saharan Africa. HASP methodologies have been incorporated in multiple WHO reports. Importantly, the donor country, Canada, has benefited in significant ways from this partnership. Operational and logistical lessons from HASP have, in turn, improved how surveillance is performed in Canada. Through this project, significant capacity was built among the staff of HASP, non-governmental organisations which were engaged as implementation partners, data coordination units which were established in each province, and in the laboratory. As is to be expected, different organisations have different agendas and priorities, requiring negotiation, at times, to ensure the success of collaborative activities. Overall, there has been considerable interest in and opportunities made for learning about the methodologies and approaches employed by HASP. Conclusions: Generally, the recognition of the strengths of the approaches and methodologies used by HASP has ensured an appetite for opportunities of mutual learning.